Social Media and Stunting Prevention Campaigns - Handayani, Bekti; Arianto, Bambang (Journal of Humanity Studies, 2023)
This research aims to elaborate on the useful role of social media as a campaign channel in preventing stunting in Indonesia. The digital era means that various daily activities of citizens are greatly influenced by social media. The benefits of social media are then used by mothers of toddlers as a channel for information, interaction, participation, decentralization, transparency and digital accountability. Social media can then be used to disseminate various information about nutrition and prevention so that it can then become educational for the public. As a result, information generated by social media has created dynamic and participatory interaction patterns. This is due to the flexibility of the features possessed by various social media platforms, especially for use as the main channel for civic information. This research uses an explanatory qualitative approach with in-depth interview techniques and observations of mothers of toddlers in the Serang Regency area, Banten Province. The research results found that social media has played a role as the main information channel in strengthening knowledge about local food and nutrition for toddlers. This research also found that social media is very effective for use as a promotional channel and stunting prevention campaign.